1997
DOI: 10.1111/j.1600-051x.1997.tb00490.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a 0.12% chlorhexidine‐digluconate‐containing mouthrinse versus a placebo on plaque and gingival inflammation over a 3‐month period

Abstract: Several previous studies have evaluated the effects of 0.12% chlorhexidine digluconate (ChD) mouthrinses on plaque and gingival inflammation. However, previously, none have been based in general dental practices. The aim of this study was to evaluate the potential to conduct controlled periodontal clinical trials in co-operation with general dental practitioners (gdps). The project took place in 5 general dental practices in the South of England. 121 healthy subjects (24 at 4 sites and 25 at the 5th), aged 18-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…Although there are many products used to control plaque and gingivitis, chlorhexidine digluconate (CHX) has received the greatest attention due to its superior clinical and microbiological effectiveness [5][6][7][8]. It is considered as the gold standard for oral antiseptics [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are many products used to control plaque and gingivitis, chlorhexidine digluconate (CHX) has received the greatest attention due to its superior clinical and microbiological effectiveness [5][6][7][8]. It is considered as the gold standard for oral antiseptics [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigating antiplaque and antigingivitis effectiveness of different CHX mouthrinse formulations on clinical periodontal parameters have shown that CHX containing mouthrinses improved the supragingival plaque control and had an additional beneficial effect on both the degree of inflammation and the microbial accumulation within the oral cavity [7,11,[20][21][22][23][24]. There has been no study that evaluated the efficacy of CHX mouthrinse in addition to daily plaque control on biochemical markers of gingival inflammation in the presence of gingivitis associated with dental plaque.…”
Section: Introductionmentioning
confidence: 99%
“…It is absorbed by the tissues and has a residual effect over time, presenting activity even 5 h after administration. (14,15) Various aspects affect oral cavity hygiene and further favor microbial growth, such as difficulty in or impossibility of self-care, presence of tracheal tube, which makes access to the oral cavity difficult, and the consequent formation of dental plaque biofilm. (10)(11)(12)16) The Centers for Disease Control and Prevention (CDC) recommends oral hygiene with chlorhexidine in patients in the perioperative period of cardiac surgery.…”
Section: Resultsmentioning
confidence: 99%
“…It has been stated that CHX mouthrinses is very efficient agent in reducing and/or preventing dental plaque [32-34] and had an additional effect on the degree of inflammation in oral cavity [3,6,32,34,35]. CHX can inhibit MMPs and prevent oxidative activation of MMPs and oxidative inactivation of α1-antitrypsin [36-38].…”
Section: Introductionmentioning
confidence: 99%